A formação docente e o uso das tecnologias digitais durante o ensino remoto na EPT – desafios e potencialidades - Heusner, Luciane Müller (2023)
The present work seeks to investigate how information and communication technologies contribute to teaching practice in the modality of remote teaching. As a general objective, we sought to analyze the contributions of different information and communication technologies in the teaching and learning process, as well as the importance of continuing education for professionals, the performance of students during and after the process of social distancing, as well as reflecting on of the methodologies and technologies used to qualify the short and long-term learning of EPT students from some Federal Institutes and Technical schools: Colégio Técnico Industrial de Santa Maria, Colégio Evangélico Panambi and the Instituto Estadual de Educação Professor Annes Dias de Cruz Alta. The methodology is based on exploratory field research with a quail-quantitative approach. As a result, it was observed that teachers found it very difficult to adapt to this new teaching format, but the gains in learning and knowledge regarding the uses of DICT pointed out by teachers were significant, awakening both teachers and students imagination. Independence and creativity to solve problems, which were previously solved in person. These advances lead to progressive transformations in education, paradigm shifts and awareness that technologies are instruments capable of modifying teaching and learning processes.